3x-6-4x-12=2x

Simple and best practice solution for 3x-6-4x-12=2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-6-4x-12=2x equation:


Simplifying
3x + -6 + -4x + -12 = 2x

Reorder the terms:
-6 + -12 + 3x + -4x = 2x

Combine like terms: -6 + -12 = -18
-18 + 3x + -4x = 2x

Combine like terms: 3x + -4x = -1x
-18 + -1x = 2x

Solving
-18 + -1x = 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-18 + -1x + -2x = 2x + -2x

Combine like terms: -1x + -2x = -3x
-18 + -3x = 2x + -2x

Combine like terms: 2x + -2x = 0
-18 + -3x = 0

Add '18' to each side of the equation.
-18 + 18 + -3x = 0 + 18

Combine like terms: -18 + 18 = 0
0 + -3x = 0 + 18
-3x = 0 + 18

Combine like terms: 0 + 18 = 18
-3x = 18

Divide each side by '-3'.
x = -6

Simplifying
x = -6

See similar equations:

| 4y-2(y-2)+5= | | 4x+18=3+8x-5 | | |-6|-|10-3|= | | 1/2+(-5/8) | | 2x+9=-97-10x | | 2/3p+1=-7 | | 5-2x+x=-10 | | 2/3+1=-7 | | -6(8m+7)= | | 7675483920129834765434x=5 | | 11-7x=59-28x | | -4x-12=-16-3x | | x^2+8x=4x | | -4x+20=-16+5x | | x/4=-3-(-7) | | -4x-7=9x+32 | | 4x+7x=2x-8 | | p=80-2qinversa | | 0.75(2x+3)-3.5=0.8(1-x) | | -5-2x+x=-10 | | a^2+a-1=o | | x=6(3.12)y | | y=6(3.12)x | | -4x-20=-16-5x | | 5+4x-x=20 | | 4x+12=16+3x | | 28c^5-8c^9= | | -3+4x-x=6 | | -6g+7g-7= | | b^2+12=0 | | 4x+4k=2x+14k | | 24/24 |

Equations solver categories